2008
DOI: 10.1111/j.1540-8175.2008.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Relationship between Metabolic Parameters and Left Ventricular Functions in Type 2 Diabetic Patients without Evident Heart Disease?

Abstract: Diastolic LV dysfunction may develop even in absence of ischemia, hypertension, and LVH in T2DM. FBG and PPG have no effect on LV functions, but HbA(1C) levels may affect diastolic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Deformation imaging would be necessary only to localize dysfunction to particular myocardial segments. Other investigators who have reported reduced longitudinal function in patients with risk factors have found similar results for either strain/strain rate or velocities 25–28 . Moreover, recent data comparing strain, by either speckle tracking or tissue Doppler, with tagged harmonic‐phase magnetic resonance imaging showed only modest correlations (r = 0.40–0.60), thus reflecting the technical challenges of these techniques 29 …”
Section: Discussionmentioning
confidence: 76%
“…Deformation imaging would be necessary only to localize dysfunction to particular myocardial segments. Other investigators who have reported reduced longitudinal function in patients with risk factors have found similar results for either strain/strain rate or velocities 25–28 . Moreover, recent data comparing strain, by either speckle tracking or tissue Doppler, with tagged harmonic‐phase magnetic resonance imaging showed only modest correlations (r = 0.40–0.60), thus reflecting the technical challenges of these techniques 29 …”
Section: Discussionmentioning
confidence: 76%
“…In diabetic hypertensive patients, concentric and eccentric left ventricular hypertrophy, increase in left ventricular muscle mass have been documented . In DM, the relationship between ABPM measurements and target organ damage has been showed in studies performed especially in adults . In this study, we planned to examine the relationship between elevated BP in diabetic children and early cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although subclinical LV dysfunction is present in very early stages in type 2 diabetic patients, there are few studies evaluating the relationship of LV dysfunction with HbA1C and blood glucose levels [26][27][28]. Most of these studies were done with conventional echocardiographic method and in some of them important parameters such as hypertension and coronary artery disease were not taken into consideration.…”
Section: Myocardial Systolic and Diastolic Dysfunction In Dm With Micmentioning
confidence: 98%